A formação em competência intercultural do estudante de comércio internacional - Martins Junior, Arlindo Maciel (My University, 2019)
The competitiveness of global markets has generated a movement in Brazil's economy. Accompanied in the last sixteen years, the country has emerged as one of the protagonists among the main players worldwide. In this flow of growth in emerging countries, there have been transformations in the ways that global transactions occur. These practices include the development of new markets, rounds of negotiations, the opening of distribution centers to expatriate employees to operate in the country where they wish to thrive. For this, it is necessary that there are professionals able to deal with the cultural differences, nuances of customs, obstacles related to the different languages. Among these abilities to deal with these challenges, academics have called these characteristics Intercultural Competence. "In this way, this work analyzes this set of skills in its different dimensions, to ascertain if students of the International Trade course have these competences with them. , it was sought to use a scale already validated in previous studies and to apply it to the students in the form of research. Methodologically, a quantitative questionnaire was used, with survey characteristics applied to the students of the International Trade Course that are of the fourth semester of graduation to verify intercultural competence and proficiency in the English language. It is concluded that students respondents of the research have high cultural competence and English proficiency considered general professional proficiency, supporting the idea that the course meets the objectives proposed in the project manager logical.(sic)
A competitividade dos mercados em nível mundial vêm gerando um movimento na economia do Brasil. Acompanhou-se nos últimos anos, o país despontar como um dos protagonistas entre os principais players mundiais. Nesse fluxo de crescimento dos países emergentes, houve transformações nas maneiras como ocorrem as transações mundiais. Dentre essas práticas, podem ser citadas desenvolvimentos de novos mercados, rodadas de negociações, abertura de centros de distribuição até a funcionários expatriados para atuar no país em que se deseja prosperar. Para isso, é necessário que existam profissionais aptos a lidarem com as diferenças culturais, nuances de costumes, entraves relativos aos diferentes idiomas. Dentre essas habilidades de lidar com os constantes desafios, os acadêmicos denominaram tais características como Competência Intercultural. Logo, este trabalho analisa o conjunto de habilidades em suas diferentes dimensões, para aferir se estudantes do curso de Comércio Internacional da Universidade de Caxias possuem essas competências consigo. Para tanto, buscou-se utilizar uma escala já validada em estudos anteriores e aplicá-la aos alunos em forma de pesquisa. Em termos metodológicos, utilizou-se um questionário quantitativo, de características survey aplicado aos alunos do Curso de Comércio Internacional que se encontram a partir do quarto semestre da graduação para verificação de competência intercultural e proficiência na língua inglesa. Conclui-se que os estudantes respondentes da pesquisa apresentam alta competência cultural e proficiência na língua inglesa considerada como proficiência profissional geral na escala ILR, embasando a ideia que o curso atende aos objetivos propostos no projeto pedagógico. (sic)
Keywords: Comércio internacional; Língua inglesa; Comunicação intercultural